Investigation of the effect of nozzle design on rheological bioprinting properties using computational fluid dynamics - Magalhães,Isabela Poley (2019)
ABSTRACT Bioprinting is the utilization of techniques derived from three-dimensional printing to generate complex biological structures which may replace natural tissues or organs. It employs high spatial resolution deposition of different cell types, growth factors and biomaterials. Those together form bioinks, which are the bioprinting inputs, analogously to conventional inks with regard to inkjet printing. In extrusion bioprinting, continuous bioink filaments are deposited layer by layer on a surface by means of an extruder nozzle, employing the displacement of a piston or pneumatic pressure. If mechanical stresses applied on a cell membrane exceed a critical value, which depends on the cell type, the cell membrane may disrupt. Computational fluid dynamics (CFD) simulations of the bioink extrusion were done to evaluate shear stresses caused by the internal pressure of extruder nozzles during bioprinting. Different three-dimensional conical nozzle designs were tested by varying angles of convergence, lengths, input diameters and output diameters of the nozzles. The power-law model, with constants k = 109.73 Pa·s0,154 and n = 0.154, was used to describe the expected non-Newtonian behavior of the bioink. Shear stresses and shear rates were evaluated for each nozzle design considering different pressures or velocities as boundary conditions at the nozzle entrance. The maximum wall shear stress value on each different nozzle varied between 1,038 Pa and 4,915 Pa. The results indicated which details of nozzle geometry are most relevant in order to optimize bioprinting. The best conditions for bioink rheology were also evaluated to ensure good printability and high cell viability.